Diagnosis of gastric carcinoma - Jandrić-Kočić Marijana C. (Association of Nurses Technicians and Midwives, 2020)
INTRODUCTION: Gastric cancer is the fourth most commonly diagnosed cancer in the world and the second most common cause of cancer mortality. Diagnosis requires histopathological analysis of tissue obtained by esophagogastroduodenoscopy or cytologic analysis of gastric wiping / flushing. CASE REPORT: Patient aged 55 years presents in a family medical clinic due to dyspeptic problems accompanied by weight loss, weakness and maladaptation present at six months. Physical examination present sensitivity to deep palpation in the epigastrium. Ultrasound abdominal examination neat, laboratory anemia present. The patient is referred for esophagogastroduodenoscopy, which corporally, on a small curve of the stomach, detects a large ulceration of the bottom covered with fibrin and detritus, femoral margins. Bioptate finding reveals the presence of ventriculi mixed adenocarcinoma (tubular adenocarcinoma cum poorly cohesive carcinoma). Computed tomography of the abdomen determines the visible thickening of the stomach in the region of small curvature in the area of dimension 110x 26 mm and a large number of individual lymph glands up to 8 mm in fat with a small curve of the stomach. A total gastrectomy with a lymphadenectomy is done at the request of the oncological consulium. The pathohistological finding after surgery is adenocarcinoma ventriculi gradus III, pT3N1Mx (small curve, part of the anterior and posterior gastric wall infiltrative, engages all layers of the wall, but does not infiltrate serosa, size 7x6 cm, R0L1V0Pn0). A re-examination of the oncology consilium indicates chemotherapy / radiotherapy in hospital conditions and thereafter 5-fluorouracil / leucovorin chemotherapy. CONCLUSION: In the absence of specific symptoms and screening and early detection capabilities, the highest number of gastric cancers is diagnosed at an advanced stage when the prognosis is poor (average survival is 24 months) and treatment options are limited. Identification of new biological / molecular markers in early diagnosis of gastric cancer would allow a better quality of life and longer survival of the diseased.